The Power of Veto by the United Nations Security Council in Warfare Protection - Alya, Nasha Rawza; Tan, Jenita; Rewiyaga, Rewiyaga (CV. Rayyan Dwi Bharata, 2024)
Since the establishment of the international organization that is the United Nations on 24 October 1945, the UN Security Council has been given the main responsibility for maintaining international harmony and prosperity as stated in article 1 of the UN Charter. One aspect that is often in the public spotlight is the use of veto rights by the 5 permanent members of the UN Security Council. The five countries that have veto rights consist of the United States, China, Russia, France and the United Kingdom. The five countries got the veto right because they had a major part in establishing the UN and to provide power and because they won World War II. The type of analysis that will be used in this analyze is normative legal analysis, this type of research aims to analyze and understand the law in terms of norms, rules, or principles governing a legal problem. The conclusion is that the veto right is not explicitly regulated in the UN Charter, but implicitly the UN Charter.